Quantifying inertia in retail deposit markets - Florian Deuflhard (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper investigates inertia within and across banks in retail deposit markets using detailed panel data on consumer choices and account characteristics. In a structural choice model, I find that costs of inertia are around one third higher for switching accounts across compared to switching within banks. Observable proxies of bank-level switching costs (number and type of additional financial products) explain most of this cost premium, while online banking usage reduces inertia. Consistent with theory, I provide evidence that banks incorporate inertia in their pricing as older accounts pay lower rates than comparable newer accounts. Counterfactual policies reducing inertia shift market share to more competitive smaller banks, but only eliminating inertia within banks already results in high potential gains in consumer surplus. This suggests that facilitating bank switching alone might be insufficient to improve consumer choices.
urn:nbn:de:hebis:30:3-472355
Keywords: 330